Conformational dynamics of 13 amino acids long NSP11 of SARS-CoV-2 under membrane mimetics and different solvent conditions. (September 2021) - Gadhave, Kundlik; Kumar, Prateek; Kumar, Ankur; Bhardwaj, Taniya; Garg, Neha; Giri, Rajanish
Abstract: The intrinsically disordered proteins/regions (IDPs/IDPRs) are known to be responsible for multiple cellular processes and are associated with many chronic diseases. In viruses, the existence of a disordered proteome is also proven and is related to its conformational dynamics inside the host. The SARS-CoV-2 has a large proteome, in which, structure and functions of all proteins are not known yet, along with non-structural protein 11 (nsp11). In this study, we have performed extensive experimentation on nsp11. Our results based on the CD spectroscopy gives characteristic disordered spectrum for IDPs. Further, we investigated the conformational behavior of nsp11 in the presence of membrane mimetic environment, α-helix inducer, and natural osmolyte. In the presence of negatively charged and neutral liposomes, nsp11 remains disordered. However, with SDS micelle, it adopted an α-helical conformation, suggesting the helical propensity of nsp11. Finally, we again confirmed the IDP behavior of nsp11 using MD simulations. In future, this conformational dynamic study could help to clarify its functional importance in SARS-CoV-2 infection. Graphical abstract: Image 1 Highlights: SARS-CoV-2 nsp11 gives characteristic disordered spectra in CD spectroscopy. MD simulation at 500 ns confirmed the IDP behaviour of nsp11. SARS-CoV-2 nsp11 adopt helical conformation in presence of SDS micelles and TFE. Negative and neutral lipids, and natural osmolyte has no effect on nsp11 conformation.